Anarchism, organization and management critical perspectives for students - Parker, Martin 1962-; Stoborod, Konstantin 1987-; Swann, Thomas 1986- (Routledge, 2020)
"You might think that anarchism and management are opposed, but this book shows how an understanding of the long history of anarchist ideas allows us to understand the problems of contemporary organizing much more clearly. Anarchism is a theory of organizing, and in times when global capitalism is in question, we need new ideas more than ever. The reader of this book will learn how anarchist ideas are relevant to today's management problems. In a series of student friendly short chapters on contemporary topics, the authors challenge the common sense that has allowed particular forms of organization and market to become globally dominant. Do we always need leaders? Is technological change always a good thing? Are markets the best way to arrange forms of exchange? This challenging book is essential for anyone who wants to understand what is wrong with business school theory, and what we might do about it. For students and teachers of management, the standard textbook reproduces the dominant ideas about the way that business should be done. This book turns those ideas on their head, asking awkward questions about authority, technology and markets, and demanding that its readers think hard about whether they want to reproduce those ideas too. Students of management, like everyone else, know that the current global system is broken but they don't know what they can do about it. This unique book uses two hundred years of anarchist ideas to give readers a clear guide for building the organizations and businesses of the future, and places choice and responsibility at the centre of making a new world for people and planet"--